Effects of Radial Rectangle Groove Width on Temperature Field of Hybrid Vehicle Wet Multi-plate Clutch - Li Dongbing (Jixie chuandong)
In order to solve the problems of higher friction temperature and short clutch life of hybrid vehicle wet multi- plate clutch,a hybrid vehicle wet multi- plate clutch is regarded as research subjects,the transient heat transfer model of wet clutch is established in engagement condition,the wet clutch friction plate radial rectangle groove width is set to analysis variables,the influences of the radial rectangle groove width on friction plate transient temperature field are got. The results show that with the increase of friction plate radial rectangle oil groove width,the wet clutch highest temperature will show a downward trend,but the friction plate temperature and friction plate geometry features exist greater relevance in the angle range,and present the characteristics of a certain period. The influences of radial rectangular oil groove width on the temperature field of wet clutch are investigated,it provides a direction to get the best rectangle oil groove width by optimization design method.